Kenya : Staff Report for the 2018 Article IV Consultation and Establishment of Performance Criteria for the Second Review Under the Stand-by Arrangement. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that Kenya has maintained strong growth in recent years. External imbalances have narrowed, strengthening resilience to shocks. The business environment continues to improve, supporting private investment. However, a severe drought, an extended presidential election, and weak bank lending-due in part to interest rate controls-slowed growth in 2017. Kenya's medium-term growth prospects are favorable, supported by infrastructure investment and an improving business environment. However, continued strong growth and macroeconomic stability hinge on the implementation of reforms. In addition, headwinds from fiscal consolidation and weak credit growth will weigh on economic activity in the near term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet